Massively parallel sequencing of forensic samples using precision ID mtDNA whole genome panel on the ion S5™ system. (December 2017) - Gouveia, N.; Brito, P.; Bogas, V.; Bento, A.M.; Balsa, F.; Serra, A.; Lopes, V.; Sampaio, L.; São Bento, M.; Cunha, P.; Porto, M.J.
Abstract: Mitochondrial DNA (mtDNA) has some unique features that make it a useful forensic marker such as absence of recombination across many generations, maternal inheritance, accumulation of mutations over time and multiple copies per cell. The application of massively parallel sequencing (MPS) to forensic genetics has expanded in recent years due to its potential to dramatically increase sample throughput, workflow efficiency and detection resolution. Recently, Applied Biosystems™ developed the Precision ID mtDNA Whole Genome Panel, specifically for mtDNA forensic applications. The preliminary results showed that mtDNA haplotypes obtained with MPS were consistent with those previously obtained with traditional Sanger sequencing, regardless of the extraction method used and pool concentration of libraries.